Heterologous Immunization With Defined RNA and Subunit Vaccines Enhances T Cell Responses That Protect Against Leishmania donovani - Duthie, Malcolm S.; Van Hoeven, Neal; MacMillen, Zachary; Picone, Alessandro; Mohamath, Raodoh; Erasmus, Jesse; Hsu, Fan-Chi; Stinchcomb, Dan T.; Reed, Steven G. (Frontiers in Immunology, 2018)
The rapid generation of strong T cell responses is also highly desirable and viral vectors can have potent CD8+ T cell-inducing activity. Immunity to leishmaniasis requires selective T cell responses, with immunization schemes that raise either CD4 or CD8 T cell responses being protective in small animal models. We have defined the leishmaniasis vaccine candidate recombinant fusion antigens, LEISH-F2 and LEISH-F3+, that when formulated in a stable emulsion with a Toll-like receptor (TLR) 4 agonist induce protective CD4+ T cell responses in animal models, as well as providing therapeutic efficacy in canine leishmaniasis and in clinical trials in leishmaniasis patients. We used the genetic sequences of these validated vaccine antigens to design RNA vaccine constructs. Immunization of mice with the RNA replicons induced potent, local innate responses that were surprisingly independent of TLR7 and activated antigen-presenting cells (APC) to prime for extremely potent antigen-specific T helper 1 type responses upon heterologous boosting with either of the subunit vaccines (recombinant antigen with second generation glucopyranosyl lipid A in stable oil-in-water emulsion; SLA-SE). Inclusion of RNA in the immunization schedule also generated MHCI-restricted T cell responses. Immunization with LEISH-F2-expressing RNA vaccine followed later by subunit vaccine afforded protection against challenge with Leishmania donovani. Together, these data indicate the utility of heterologous prime-boost immunization schemes for the induction of potent antigen-specific CD4 and CD8 T cell responses for protection against intracellular pathogens.